2015
DOI: 10.1080/10926755.2014.895467
|View full text |Cite
|
Sign up to set email alerts
|

Racialization, Othering, and Coping Among Adult International Adoptees in Finland

Abstract: This qualitative interview study examined experiences of racialization and coping among 14 adult international adoptees in Finland. The results show that adoptees encounter a range of racializations by which they are made 'other' and excluded from Finnishness. Racialization mostly occurs indirectly and subtly, and often by significant others, and consequently is more difficult to cope with. The findings suggest that the Finnish adoption community and adoption research should pay more attention to experiences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
11
0
4
Order By: Relevance
“…Due to this position, they experience less discrimination than other ethnic minorities do. However, it is possible that, because of their sociocultural and adoption status, adoptees may encounter vicarious and subtle forms of racism that are often difficult to notice (Koskinen, 2014b). Although the mean of perceived racial/ethnic discrimination might appear low, it could be assumed that many areas of adoptees' life have been influenced by discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this position, they experience less discrimination than other ethnic minorities do. However, it is possible that, because of their sociocultural and adoption status, adoptees may encounter vicarious and subtle forms of racism that are often difficult to notice (Koskinen, 2014b). Although the mean of perceived racial/ethnic discrimination might appear low, it could be assumed that many areas of adoptees' life have been influenced by discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited in number, a few qualitative studies on adoptees' experiences of discrimination in Finland have indicated that despite fulfilling all the criteria of Finnish nationality and culture, especially the nonwhiteness of adoptees makes them vulnerable to racism (e.g., Koskinen, 2014b;Rastas, 2009). A number of other Scandinavian qualitative adoption studies have consistently indicated that nonwhite international adoptees experience multiple forms of discrimination varying from its most blatant forms to the covert forms of everyday racism and institutionalized racism (Hübinette & Andersson, 2012;Hübinette & Tigervall, 2009;Lind, 2012;Lindblad & Signell, 2008;Tigervall & Hübinette, 2010).…”
mentioning
confidence: 99%
“…[...] And your family, don't they get shocked or something when you come back with the child? (Lebohang,19,pregnant) The birth mothers' concern about racism resonates with what many adult adoptees have recalled about their experiences: According to the findings of this research, adoptees of colour have been targets of racialised micro-and macro-aggression (Koskinen 2015), gazes and racism (Hübinette & Tigervall;Rastas 2007). The experiences of adoptees and the fears of birth mothers are strangely contradictory to the views of most adoptive parents and the general accepted way of talking about adoption.…”
Section: 'Is She a Black Child?'mentioning
confidence: 52%
“…Colour-blindness in this sense points to the unwillingness to acknowledge the continuing salience of race in society. Many adoptive parents may not be aware of the everyday racism their children encounter outside the home (Koskinen 2015;Rastas 2007;Ruohio 2009), or of their own racial privilege (see Bashi Treitler 2014). These birth mothers, however, were very aware of how racism operates.…”
Section: 'Is She a Black Child?'mentioning
confidence: 99%
“…The experiencing of racism was common across the sample of intercountry adoptees of all ages who took part in the study. Often this is expressed in subtle ways, such as in misrecognition or where community members routinely ask, ‘Where are you from?’ (Koskinen, 2015). Despite having an Australian accent, the adoptees said that this was a frequent question put to them, asking them to account for how they fit in as an ‘Australian’ when they look ‘Asian’.…”
Section: Resultsmentioning
confidence: 99%